Primary Villoglandular Mucinous Adenocarcinoma of the Vulva - Akiko Matsuzaki; Masanao Saio; Noritake Kosuge; Hajime Aoyama; Tomoko Tamaki; Hirofumi Matsumoto; Naoki Yoshimi (Hindawi Limited, 2017)
Primary villoglandular mucinous adenocarcinoma of the vulva is rare tumor. We report a case of 68-year-old woman who developed this very uncommon malignant tumor. Immunohistochemical examination of this tumor revealed positive staining for Cytokeratin 20, Mucin 2, and CDX2, although Cytokeratin 7 and Mucin 6 were negative. This positive staining indicated the tumor enteric type characters. In order to exclude the possibility of the metastasis from another site, we thoroughly evaluated clinical data and extensively investigated the whole body. However, we could not detect any other tumors. The patient was treated by tumor resection. The patient remains free of disease 5 years after surgery.